Endogenous Coordination: Multinational Companies and the Production of Collective Goods in Central and Eastern Europe - Bob Hancké (London School of Economics and Political Science (LSE), European Institute, 2011)
Most accounts of business coordination assume historically given conditions for this to emerge. Business coordination is therefore difficult, perhaps impossible, to construct endogenously. This paper examines a process of 'endogenous coordination' through an analysis of reindustrialization and industrial upgrading in Central Europe during the 2000s. Because of its recent post-communist history, during which existing institutions of economic governance were dismantled wholesale, Central Europe is a particularly unlikely place for complex forms of business coordination to emerge. Demonstrating the empirical possibility of endogenous coordination, and identifying conditions under which it has emerged thus shifts the debate from pessimistic fatalism to a more optimistic world of possibility. The paper identifies three conditions for business coordination to emerge. One, a pattern of industrialization that combines sophisticated skills and capital goods, leading to higher asset specificity and fixed costs; two, bottlenecks in the production of collective goods associated with these assets against the background of potentially high returns in investment; and, three, the existence of a third party, which provides a forum for deliberation and strategic coordination while holding effective sanctioning capacity.
Keywords: 330